Debris collected in-situ from spontaneously ruptured atherosclerotic plaque invariably contains large cholesterol crystals and evidence of activation of innate inflammation: Insights from non-obstructive general angioscopy. (July 2022) - Komatsu, Sei; Yutani, Chikao; Takahashi, Satoru; Takewa, Mitsuhiko; Ohara, Tomoki; Hirayama, Atsushi; Kodama, Kazuhisa
Abstract: Background and aims: Development and expansion of cholesterol crystals (CCs) within a lipid rich atherosclerotic core are believed to predispose to plaque rupture. We have used non-obstructive general angioscopy to described a range of appearances of spontaneously ruptured atherosclerotic plaques (SRAPs) in the aorta in-situ, and have confirmed that debris extruding from some SRAPs (puff-chandelier lesions) are rich in cholesterol crystals and leukocytes. The purpose of this study was to characterized the nature of the inflammatory infiltrate of this debris. Methods: Debris was collected from puff-chandelier lesions at the time of angioscopy in patients with known coronary disease. Prepared specimens were examined by light microscopy, and immunostaining was used to detect markers of activation of the innate inflammatory pathway including CD68, NLRP3, caspase-1, IL-1β, IL-18, and IL-6. Results: We analysed debris sampled from 20 puff-chandelier lesions. Microscopy confirmed the presence of large CCs, macrophages, fibrin, calcified gruel, lymphocytes, and neutrophils in 100%, 100%, 95%, 25%, 20%, and 15% of the specimens respectively. Immunostaining confirmed the presence of CD68, NLRP3, IL-1β, and IL-6 within the debris in 100%, 90%, 80%, and 80%, of the specimens respectively. CCs, NLRP3, caspase-1, IL-1β, IL-18, were also identified in the cytoplasm of macrophages. Conclusions: Debris from SRAPs with a puff-chandelier appearance invariably contained large CCs associated with a range of activated leukocytes involved in innate inflammation. This observation supports the thesis that the development and enlargement of CCs in the core of lipid rich plaques may precipitate traumatic and inflammatory injury that may lead to plaque rupture. Graphical abstract: Image 1 Highlights: ● Cholesterol crystals (CCs) may activate NLRP3 inflammasomes. ● SRAPs were rich in CCs and leukocytes. ● Atherosclerotic debris may embolise leading to ischemic and inflammatory tissue injury.